GARDENING COCONUT FARMERS LOCAL WISDOM IN THE VILLAGE TOPANG KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Nurul Anjani; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research purpose of this study to analyze how the behavior of farmers in the Topang which has palm plantation which starts from clearing, processing, nursery, plant up to collect the results and the behavior of the last farmers in preparing the land. farmers cleared the land himself with reason as a source of livelihood. Farmers who cultivate farming land with their own hands, without having to hire someone else to do it. To be a successful farmer should do their own farmers to comply with what is expected by each farmer. The first beginning farmers develop their plantations without government permission letter regarding land ownership in processed by farmers because the government has not contributed at that time. Behavior of farmers in processing a piece of land to plantations was not using it by burning palm plantation farmers use the traditional way to keep the preservation of the environment. Their behavior shows that there must be a way to burn to cultivate a piece of land, but there are many more ways to do it wisely. The behavior of farmers who are still stuck with the old ways that do not cause damage to the function of forests. The accusations being leveled at farmers who cultivate land by burning was never true. Because farmers clearing land must pass through that long to work his land.Keywords: local knowledge, behaviors, the farming community garden